1975
DOI: 10.1145/321906.321917
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Several Task-Scheduling Algorithms for a Model of Multiprogramming Computer Systems

Abstract: ABST~tACT. In multiprogramming computer systems, the scheduling strategy used to select tasks to be activated is an important factor in the achievement of the performance goals of the system. One form of analysm of scheduling algorithms represents the system as an abstract model of computation and then formally analyzes the algorithms operating in the context of the model. This paper presents an abstract system model which consists of several identical and independent task processors and a memory of arbitrary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

1978
1978
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(71 citation statements)
references
References 7 publications
0
69
0
1
Order By: Relevance
“…Bin packing with cardinality constraints (and regular, non-splittable items) was introduced and studied in an offline environment as early as in 1975 by Krause, Shen and Schwetman [12,13]. They showed that the performance guarantee of the well known First Fit algorithm is at most 2.7 − 12 5k .…”
Section: { A(i) Opt(i) |Opt(i) = N}mentioning
confidence: 99%
“…Bin packing with cardinality constraints (and regular, non-splittable items) was introduced and studied in an offline environment as early as in 1975 by Krause, Shen and Schwetman [12,13]. They showed that the performance guarantee of the well known First Fit algorithm is at most 2.7 − 12 5k .…”
Section: { A(i) Opt(i) |Opt(i) = N}mentioning
confidence: 99%
“…Cardinality constrained bin packing was studied in the offline environment already in 1975 by Krause, Shen and Schwetman [12,13]. They showed that the performance guarantee of the well known First Fit algorithm is at most 2.7 − 12 5k .…”
Section: A(σ) Op T (σ)mentioning
confidence: 99%
“…This problem was studied also in [17,10,4]. Cardinality constrained bin packing was first studied by Krause, Shen and Schwetman [18,19]. It was also studied in [3,8].…”
Section: Introductionmentioning
confidence: 99%